2020
DOI: 10.3390/foods9111570
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Process Lethality (5-Log Reduction) of Salmonella and Salt Concentration during Sodium Replacement in Biltong Marinade

Abstract: Salt (sodium chloride, NaCl) is commonly used in ready-to-eat (RTE) meat products such as biltong, a South African style dried beef product for flavor, enhanced moisture loss, and reduction of microbial growth. However, increased consumption of high sodium content foods is commonly associated with high blood pressure and heart disease. This study evaluated the use of alternative salts, potassium chloride (KCl) and calcium chloride (CaCl2) in the biltong marinade to achieve a ≥ 5-log reduction of Salmonella, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Because of the thickness of biltong beef, vacuum tumbling raises a concern as 'nonintact beef' (a safety concern for USDA-FSIS) that could have issues related to internalization of S. aureus that might result in production of staphylococcal enterotoxin if growth and conditions allowed. Our prior work showed that biltong made with 2.2% NaCl in the total biltong marinade formulation (including the weight of beef) approaches a moisture loss of ~60%, an internal Aw of 0.82 (Aw of 0.69 for ground biltong), a biltong pH of ~5.26, The data presented herein demonstrate that a basic biltong process and marinade composed of spices (pepper, coriander), salt, and vinegar, applied during vacuum tumbling for 30 min and followed by drying at 23.9 • C (75 • F) and 55% RH can result in ≥5-log reduction (in 5-7 days) with Salmonella serovars [9,10], as well as E. coli O157:H7, L. monocytogenes, and S. aureus (this study) (Figure 9). The 4 major groups of foodborne pathogens that could be associated with raw beef and potentially a concern for survival during the biltong process react similarly when subjected to the basic biltong process used in this study (Figure 9).…”
Section: Analysis Of Staphylococcal Enterotoxin a (Sea) And B (Seb) D...mentioning
confidence: 61%
See 3 more Smart Citations
“…Because of the thickness of biltong beef, vacuum tumbling raises a concern as 'nonintact beef' (a safety concern for USDA-FSIS) that could have issues related to internalization of S. aureus that might result in production of staphylococcal enterotoxin if growth and conditions allowed. Our prior work showed that biltong made with 2.2% NaCl in the total biltong marinade formulation (including the weight of beef) approaches a moisture loss of ~60%, an internal Aw of 0.82 (Aw of 0.69 for ground biltong), a biltong pH of ~5.26, The data presented herein demonstrate that a basic biltong process and marinade composed of spices (pepper, coriander), salt, and vinegar, applied during vacuum tumbling for 30 min and followed by drying at 23.9 • C (75 • F) and 55% RH can result in ≥5-log reduction (in 5-7 days) with Salmonella serovars [9,10], as well as E. coli O157:H7, L. monocytogenes, and S. aureus (this study) (Figure 9). The 4 major groups of foodborne pathogens that could be associated with raw beef and potentially a concern for survival during the biltong process react similarly when subjected to the basic biltong process used in this study (Figure 9).…”
Section: Analysis Of Staphylococcal Enterotoxin a (Sea) And B (Seb) D...mentioning
confidence: 61%
“…The data presented herein demonstrate that a basic biltong process and marinade composed of spices (pepper, coriander), salt, and vinegar, applied during vacuum tumbling for 30 min and followed by drying at 23.9 °C (75 °F) and 55% RH can result in ≥5-log reduction (in 5–7 days) with Salmonella serovars [ 9 , 10 ], as well as E. coli O157:H7, L. monocytogenes , and S. aureus (this study) ( Figure 9 ). The 4 major groups of foodborne pathogens that could be associated with raw beef and potentially a concern for survival during the biltong process react similarly when subjected to the basic biltong process used in this study ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The number of Salmonella was reduced. It was shown that the use of salt substitutes in the marinade would allow the preparation of healthy and safe meat products with reduced salt content [ 161 ].…”
Section: Salt Content Reduction and Its Consequencesmentioning
confidence: 99%